Jolotundo As an Attraction of Local Wisdom Based Ecotourism - Basalamah, Muhammad Ridwan; Hariri, Hariri (Local Wisdom : Jurnal Ilmiah Kajian Kearifan Lokal, 2020)
Tourism has now developed into one of the largest industries in various parts of the world by providing many benefits in each sector In addition this study also aims to determine whether there is an influence of the perception of tourists in the Jolotundo area as an ecotourism attraction in the village of Seloliman. Ethnography was used to conduct this study. Qualitative data related to local wisdom were obtained through several techniques. Interview and observation were used to gain the main data, while secondary data were taken from related document analysis. The result The most frequent activity of visitors to Jolotundo is at night. On certain nights, such as on the full moon night, Friday night legi, 1 muharram night, and on the night of one Suro. On that night Jolotundo was full of pilgrims, many thousands of pilgrims came to hold rituals with a specific purpose. Every day the Jolotundo temple is crowded by visitors. Many of them are carrying out activities in the temple. Every activity carried out by the community varies depending on their desires and beliefs. Some visitors who come to Petirtaan Jolotundo also have a need for recreation "refreshing the mind" and can also be used for study tours because the natural panorama of Petirtaan Jolotundo tourism is indeed very beautiful and cool on the western slope of Mount Penanggungan, so it also right to refresh the mind.Â DOI:Â https://doi.org/10.26905/lw.v12i2.4144